The Effect of the Mentimeter Application-Based PBL Model on Student Learning Interests in Science Learning Courses Integrated with Religious Values - Nurhasnawati Nurhasnawati; Apriliyanti Muzayanati; Ichsan Ichsan (Postgraduate, University of Mataram, 2023)
Learning is a process in which there are various elements and components. The purpose of all of that is for students to know, be skilled and become better. Moreover, learning is done online, student interest in learning is rather low because the delivery can only be discussed, so researchers use models and media to increase student interest. the purpose of this study was to determine student interest before and after receiving treatment. The method used is quantitative in the form of a quantitative method. Pre-experimental design is a design that includes only one group or class given pre- and post-test research subjects of 35 students. As for the results of the study, the normality test indicates that the data is normally distributed, that the probability value > of 0.05 then Ho is accepted in the sense that the above data is normally distributed. In addition to the normality test, there is also a homogeneity test in which the results of the test show that the data is homogeneous. that the value of sig. > 0.05, which is the sig. value of the data above 0.091, it can be said that the variances of two or more groups have the same data population. After the normality and homogeneity tests, the researcher analyzed the data using the Paired sample t-test and found that the sig. (2-tailed) is 0.000 less than 0.05, it can be concluded that there is a difference between not using the minute-meter-based PBL model and using the minute-meter-based PBL model